A unique new species of genus Neocyrtopsis Liu & Zhang, 2007 (Orthoptera: Tettigoniidae: Meconematinae) from Taiwan - Chen, Po-Wei; Wu, Shipher (Zootaxa, 2025)
In this study a new species of Neocyrtopsis Liu & Zhang, 2007 from Taiwan is described, a key to all known species is provided. Variations in characteristics among species and the distribution pattern of the genus are also discussed. All specimens will be deposited in National Taiwan Museum, Taipei, Taiwan (NTM).